2022
DOI: 10.1101/2022.01.06.472721
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

STREAMING-tag system reveals spatiotemporal relationships between transcriptional regulatory factors and transcriptional activity

Abstract: Transcription is a dynamic process that stochastically switches between the ON and OFF states. To detect the dynamic relationship among protein clusters of RNA polymerase II (RNAPII) and coactivators, gene loci, and transcriptional activity, we inserted an MS2 repeat, a TetO repeat, and inteins with a selection marker just downstream of the transcription start site (TSS). By optimizing the individual elements, we have developed the Spliced TetO REpeAt, MS2 repeat, and INtein sandwiched reporter Gene tag (STREA… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 68 publications
0
0
0
Order By: Relevance
“…Further, the formation of Pol II clusters in zebrafish embryos could be reproduced by simulations of surface condensation, where regulatory chromatin acts as a condensation surface [30]. Previous work found that, once formed, transcriptional clusters can also exhibit an internal spatial organization, including compartments at the scale of ∼100 nm that correspond to consecutive steps of transcription regulation [9,10,21,74]. Separation of Pol II recruitment and transcript elongation, for example, could be explained in terms of the exclusion of transcribed genes and their RNA transcripts from a liquid phase enriched in recruited Pol II [11,75].…”
Section: Discussionmentioning
confidence: 97%
“…Further, the formation of Pol II clusters in zebrafish embryos could be reproduced by simulations of surface condensation, where regulatory chromatin acts as a condensation surface [30]. Previous work found that, once formed, transcriptional clusters can also exhibit an internal spatial organization, including compartments at the scale of ∼100 nm that correspond to consecutive steps of transcription regulation [9,10,21,74]. Separation of Pol II recruitment and transcript elongation, for example, could be explained in terms of the exclusion of transcribed genes and their RNA transcripts from a liquid phase enriched in recruited Pol II [11,75].…”
Section: Discussionmentioning
confidence: 97%